Literature Review: The Role Of Intrinsic And Extrinsic Motivation In Improving Employee Performance - Stella Sitorus, Maris; Humairah, Siti; Sanjaya Sembiring, Robert; F. Dalimunthe, Ritha (CV RIFAINSTITUT, 2024)
The importance of the role of employees as motor drivers in the organization so that employees are expected to be able to work more productively and professionally by being driven by a sense of security in carrying out all their activities. Intrinsic motivation and extrinsic motivation can provide more concrete encouragement in achieving company targets. Intrinsic and extrinsic motivation have different characteristics but complement each other in efforts to improve performance. Intrinsic motivation tends to produce ongoing commitment and satisfaction in work, which has a positive impact on employee creativity and innovation. On the other hand, extrinsic motivation can provide more concrete encouragement in achieving company targets, especially in the short term. Research Methods Used Literature review which aims to analyze in depth the role of intrinsic and extrinsic motivation on employee performance, with the aim of providing insights that can be used as a basis for managerial decision making related to human resource management in the organization. The results of the literature review show that the influence of intrinsic and extrinsic motivation on employee performance is very significant. The influence of intrinsic motivation through the context of involvement, creativity, work quality, resilience, and well-being, while through financial incentives, non-financial rewards, and recognition in the work environment. The conclusion of this journal is that employees who have high motivation tend to show better performance in the tasks given, achieve goals faster, and produce higher quality output.